K-State Turfgrass Research 2013 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
Turfgrass Research 2013 contains results of projects conducted by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day, August 1, 2013, at the John C. Pair Horticulture Research Center in Haysville, Kan. Articles included in this Report of Progress present summaries of research projects that were completed recently or will be completed in the next year or two. Specifically, this year’s report presents summaries of research on turf establishment and management, variety evaluations, pest management, and water issues and drought.
Keywords: Turfgrass; Kansas; Pest management; Water management; Drought